Gene Polymorphism Vitamin D receptor FokI in Thalassemia Children in AL-Muthanna Province (Medico Legal Update, 2019)
Background and Objective: Vitamin D receptor is considered genetic variants that related with vitaminD status. Our study was recorded polymorphism in vitamin D receptor (VDR) FokI in beta thalassemiachildren. In this study has been shown polymorphism VDR FokI dominant (FF) ,hybrid(Ff).VDR is includesa beginning codon polymorphism (BCP) that consist of three codon above the course of a second beginningsite (ATG).The BCP can be located by the restriction enzyme Fok I,which allele(f)references first of therestriction site ATG is presents, whereas the allele(F) references its missing . Materials and Methods: Inthis study vitamin D3 levels were evaluated by Enzyme Linked Immunosorbent Assay(Elisa).FokI genepolymorphism were analyzed by using polymerase chain reaction- restriction fragment length polymorphismassay (PCR-RFLP) were estimated in 50 participants children beta thalassemia were distributed to 25 maleand 25 female. Results: Patients had significant decrease vitamin D and serum calcium p=0.084 and p=0.751respectively, alkaline phosphate was recorded p=0.665, potassium= 0.278 and total protein p=0.521. in themale study 84% had VD insufficiency and 16% deficiency ,female study 96%had VD insufficiency and4% deficiency . Conclusion: Vitamin D3 was higher in female more than male and recorded in age category9-12 years old .VDR FokI gene polymorphism effect VD status ,genotype FF,Ff appeared in our study andabsence genotype ff.